2015
DOI: 10.1242/jeb.116012
|View full text |Cite
|
Sign up to set email alerts
|

Hearing of the African lungfish (Protopterus annectens) suggests underwater pressure detection and rudimentary aerial hearing in early tetrapods

Abstract: In the transition from an aquatic to a terrestrial lifestyle, vertebrate auditory systems have undergone major changes while adapting to aerial hearing. Lungfish are the closest living relatives of tetrapods and their auditory system may therefore be a suitable model of the auditory systems of early tetrapods such as Acanthostega. Therefore, experimental studies on the hearing capabilities of lungfish may shed light on the possible hearing capabilities of early tetrapods and broaden our understanding of hearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 31 publications
2
34
1
Order By: Relevance
“…By contrast, the lungs of both juvenile and adult awake axolotls contained 2-3 ml air, which, compared with a model of fish swim-bladder vibrations [12], corresponds to a resonance frequency of 4-500 Hz. This finding matches the frequency range where axolotls can detect the sound pressure (figure 3a), suggesting that axolotls sense the underwater sound pressure by detecting the pressure-induced particle motion caused by the air volumes in their lungs, as seen in lungfish [30].…”
Section: (A) Underwater Sound Detectionsupporting
confidence: 75%
See 2 more Smart Citations
“…By contrast, the lungs of both juvenile and adult awake axolotls contained 2-3 ml air, which, compared with a model of fish swim-bladder vibrations [12], corresponds to a resonance frequency of 4-500 Hz. This finding matches the frequency range where axolotls can detect the sound pressure (figure 3a), suggesting that axolotls sense the underwater sound pressure by detecting the pressure-induced particle motion caused by the air volumes in their lungs, as seen in lungfish [30].…”
Section: (A) Underwater Sound Detectionsupporting
confidence: 75%
“…The high sensitivity is underlined by the fact that thresholds determined by evoked potentials may be 10-30 dB above thresholds determined by single cell recordings or behavioural studies in a variety of animals [39 -41]. Moreover, the low-frequency vibration sensitivity found here is comparable with the vibration sensitivity of lungfish [30,42] in terms of best frequency and sensitivity, but whereas the lungfish vibrogram is U-shaped, the salamander vibrograms were W-shaped, having an additional peak at higher frequencies. In frogs, both the saccule and the amphibian papilla are involved in detection of substrate vibrations: the saccule being most sensitive at frequencies below 100 Hz, and the amphibian papilla to frequencies between 60 and 600 Hz [43][44][45].…”
Section: (B) Detection Of Substrate Vibrationssupporting
confidence: 52%
See 1 more Smart Citation
“…Prior studies in other taxa demonstrated that fishes can detect sound pressure in the absence of a clear connection ( Figure 12D). This has been shown in the genus Stegastes (family Pomacentridae, damselfishes; Myrberg and Spires, 1980), Gadus (family Gadidae, cods; Sand and Enger, 1973), and recently in the African lungfish Protopterus (family Protopteridae, lungfishes, Christensen et al, 2015). It is assumed that in these families bladder wall oscillations are transmitted to the inner ears via the interjacent tissue (Hawkins, 1986).…”
Section: Cichlidaementioning
confidence: 96%
“…To date it remains elusive how certain inner ear modifications are correlated to certain aspects of auditory abilities. Moreover, only few studies successfully disentangle the detection of the amounts of particle motion and sound pressure in fishes (e.g., Myrberg and Spires, 1980;Christensen et al, 2015).…”
Section: Modified Otolith End Organs In Teleostsmentioning
confidence: 99%